SEDIMENTS POLLUTION WITH HEAVY METALS. CASE STUDY: BAIA MARE MINING AREA. - PIŞTEA IOANA; ROŞU CRISTINA; ROBA CARMEN; OZUNU AL. (Aerul şi Apa: Componente ale Mediului, 2015)
The purpose of this research was to assess the degree of sediments contamination with heavy metals. In December 2013, 8 sediments samples were collected from several areas from Baia Mare. Each of the collected sediment samples was analyzed for pH, redox potential (ORP), electrical conductivity (EC), total dissolved solids (TDS) and salinity with a portable multiparameter (WTW 3210i). In laboratory, using an ICP-OES, all the sediment samples were analyzed for iron (Fe), nickel (Ni), chromium (Cr), cobalt (Co), copper (Cu), zinc (Zn), cadmium (Cd), lead (Pb), and manganese (Mn).According to Romanian legislation the level of Cd, Cu, Pb and Zn exceeded the maximum permissible limit (0.8 mg/kg, 40 mg/kg, 85 mg/kg and 150 mg/kg).Heavy metals are not removed from aquatic ecosystem by self purification and they can accumulate in suspanded particulates and sediments, as a consequence they are a real threath for the human health and ecosystem via food chain accumulation.